Polymer fuel cells. Part II. Types of polymers and applications - Malinowski, M.; Iwan, A. (Polimery, 2014)
In the first part of this review the mechanism of operation and kinds of fuel cells along with experimental methods used were described. The following second part of the review includes the description of different kinds of polymers intended for fuel cells such as: (i) fluorinated polymers, (ii) sulfonated polymers and (iii) aromatic polymers. Advantages and disadvantages of each polymer in view of its use in various types of fuel cells were shown. The possibility to prepare the blends of polymers [Nafion®, poly(vinylidene fluoride) (PVDF), poly(2,6-dimethyl-1,4-phenylene oxide) (PPO)] and poly(benzimidazole) (PBI) with organic (imidazole, diethyl amine or PBI) and inorganic (ZrP, SiO2, TiO2, BPO4, H3PO4, Sn0,95Al0,05P2O7-PxOy, CsHSO4) additives was discussed. Examples of applications of fuel cells divided with respect to the manner of their use: mobile, stationary and for transportation purposes were given.